2022
DOI: 10.1155/2022/4829943
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitic Infections among Diabetic Patients in Tertiary Care Hospital

Abstract: Background and Aims. This study was conducted to investigate intestinal parasitic infections among diabetes patients compared to nondiabetic (control) individuals and examine the intensity of parasitosis in both groups. Even though diabetes poses a risk for parasitic infections, similarly, few recent studies suggest that parasitic infections, especially toxoplasmosis, and cysticercosis affecting pancreatic cells, can cause a decrease in insulin secretion, thus leading to diabetes. A retrospective study was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Thus the immunosuppression mediated by these underlying comorbidities was explained by a study by Khanna et al . [ 28 ] validates the lack of an intact immune system to defend one’s body from the effect of parasitic infections. While the above-mentioned study demonstrated a high incidence of helminthic infection in diabetics,[ 28 ] in contrast, the diabetic patients in this study were more prone to intestinal parasitic infections by protozoans namely Giardia lamblia .…”
Section: Discussionmentioning
confidence: 95%
“…Thus the immunosuppression mediated by these underlying comorbidities was explained by a study by Khanna et al . [ 28 ] validates the lack of an intact immune system to defend one’s body from the effect of parasitic infections. While the above-mentioned study demonstrated a high incidence of helminthic infection in diabetics,[ 28 ] in contrast, the diabetic patients in this study were more prone to intestinal parasitic infections by protozoans namely Giardia lamblia .…”
Section: Discussionmentioning
confidence: 95%
“…Before the fltration process, 10% formalin is used as a fxative that preserves the integrity of cysts and trophozoites that might be present in the specimen. Te diethyl ether dissolves debris and the centrifugation process concentrates and sediments the enteric parasites for examination [38]. For diagnostics and detection rate, the modifed Ziehl-Neelsen staining method was able to detect more of the intestinal coccidian compared to formol-ether concentration targeting both the intestinal coccidian and other enteric protozoa and the least performed is the direct wet mount technique.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of microbial flora in the human body has aroused extensive concern. It not only plays an important role in the intestine, which is widely studied nowadays, but also gradually functions in other organ systems (Champer et al, 2018;Khanna et al, 2022). Nowadays, researchers pay more and more attention to women's health, especially the vaginal microbiota, since the vagina has a huge microecosystem containing billions of species of microorganisms (Witkin and Forney, 2020).…”
Section: Introductionmentioning
confidence: 99%